Machine learning in the prediction of post-stroke cognitive impairment: a systematic review and meta-analysis - Li, XiaoSheng; Chen, Zongning; Jiao, Hexian; Wang, BinYang; Yin, Hui; Chen, LuJia; Shi, Hongling; Yin, Yong; Qin, Dongdong (Frontiers in Neurology, 2023)
Objective Cognitive impairment is a detrimental complication of stroke that compromises the quality of life of the patients and poses a huge burden on society. Due to the lack of effective early prediction tools in clinical practice, many researchers have introduced machine learning (ML) into the prediction of post-stroke cognitive impairment (PSCI). However, the mathematical models for ML are diverse, and their accuracy remains highly contentious. Therefore, this study aimed to examine the efficiency of ML in the prediction of PSCI. Methods Relevant articles were retrieved from Cochrane, Embase, PubMed, and Web of Science from the inception of each database to 5 December 2022. Study quality was evaluated by PROBAST, and c-index, sensitivity, specificity, and overall accuracy of the prediction models were meta-analyzed. Results A total of 21 articles involving 7,822 stroke patients (2,876 with PSCI) were included. The main modeling variables comprised age, gender, education level, stroke history, stroke severity, lesion volume, lesion site, stroke subtype, white matter hyperintensity (WMH), and vascular risk factors. The prediction models used were prediction nomograms constructed based on logistic regression. The pooled c-index, sensitivity, and specificity were 0.82 (95% CI 0.77–0.87), 0.77 (95% CI 0.72–0.80), and 0.80 (95% CI 0.71–0.86) in the training set, and 0.82 (95% CI 0.77–0.87), 0.82 (95% CI 0.70–0.90), and 0.80 (95% CI 0.68–0.82) in the validation set, respectively. Conclusion ML is a potential tool for predicting PSCI and may be used to develop simple clinical scoring scales for subsequent clinical use. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=383476.